2015
DOI: 10.1007/s11356-015-5274-0
|View full text |Cite
|
Sign up to set email alerts
|

Experiments in water-macrophyte systems to uncover the dynamics of pesticide mitigation processes in vegetated surface waters/streams

Abstract: Knowledge on the dynamics and the durability of the processes governing the mitigation of pesticide loads by aquatic vegetation in vegetated streams, which are characterized by dynamic discharge regimes and short chemical residence times, is scarce. In a static long-term experiment (48 h), the dissipation of five pesticides from the aqueous phase followed a biphasic pattern in the presence of aquatic macrophytes. A dynamic concentration decrease driven by sorption to the macrophytes ranged from 8.3 to 60.4% fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The presence of densely rooted cattails ( Typha sp. ), a common macrophyte found in North American wetlands, along the channel’s margins can further facilitate in slowing water movement and the adsorption and uptake of pesticides (Main et al 2017 ; Moore et al 2017 ; Stang et al 2016 ). Hunt et al ( 2007 ) found that the system reduced pesticide concentrations, particularly the frequently detected organophosphate insecticide diazinon, and associated aquatic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of densely rooted cattails ( Typha sp. ), a common macrophyte found in North American wetlands, along the channel’s margins can further facilitate in slowing water movement and the adsorption and uptake of pesticides (Main et al 2017 ; Moore et al 2017 ; Stang et al 2016 ). Hunt et al ( 2007 ) found that the system reduced pesticide concentrations, particularly the frequently detected organophosphate insecticide diazinon, and associated aquatic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…These methods may need further refinement to address emerging pesticides, such as neonicotinoids. Because of their high solubility, vegetation does not sorb these pesticides (Stang et al 2015), so carbon treatment (Voorhees et al 2017) or system designs that promote further solar or bacterial degradation may be necessary.…”
Section: Management Vision—approaches Tailored To Agricultural and Urban Pesticidesmentioning
confidence: 99%
“…Many water soluble pesticides such as neonicotinoids are not effectively treated by VTS (Stang et al 2016) and the use and detections of this class of insecticides are increasing in agricultural regions of California (Deng 2015;Deng et al 2019). Imidacloprid is used in conjunction with pyrethroids on most lettuce crops in the Salinas Valley, and has recently been detected in irrigation runoff in the central coast region.…”
Section: Introductionmentioning
confidence: 99%